Comparison between percutaneous and laparoscopic microwave ablation of hepatocellular carcinoma. (1st January 2020) - Della Corte, Angelo; Ratti, Francesca; Monfardini, Lorenzo; Marra, Paolo; Gusmini, Simone; Salvioni, Marco; Venturini, Massimo; Cipriani, Federica; Aldrighetti, Luca; De Cobelli, Francesco
Abstract: Background: Based on patient and tumor characteristics, some authors favor laparoscopic microwave ablation (LMWA) over the percutaneous approach (PMWA) for treatment of hepatocellular carcinoma (HCC). We compared the two techniques in terms of technique efficacy, local tumor progression (LTP) and complication rates. Study design: A retrospective comparative analysis was performed on 91 consecutive patients (102 HCC tumors) who underwent PMWA or LMWA between October 2014 and May 2019. Technique efficacy at one-month and LTP at follow-up were assessed by contrast-enhanced CT/MRI. Kaplan–Meier estimates and Cox regression were used to compare LTP-free survival (LTPFS). Results: At baseline analysis, LMWA group showed higher frequency of multinodular disease ( p  < .001) and average higher energy delivered over tumor size ( p  = .033); PMWA group showed higher rates of non-treatment-naïve patients ( p  = .001), patients with Hepatitis-C ( p  = .03) and BCLC-A1 disease ( p  = .006). Technique efficacy was not significantly different between the two groups ( p  = .18). Among effectively treated patients, 75 (83 tumors) satisfied ≥6 months follow-up, 54 (57 tumors) undergoing PMWA and 21 (26 tumors) LMWA. LTP occurred in 14/83 cases (16.9%): 12 after PMWA (21.1%) and 2 after LMWA (7.7%). At univariate analysis, technique did not correlate to LTPFS ( p  = .28). Subgroup analysis showed a trend toward worse LTPFS after PMWA of subcapsular tumors ( p  = .16). Major complications were observed in six patients (6.6%), 2 after PMWA and 4 after LMWA (3.2% vs 14.3%, p  = .049). Conclusions: Technical approach did not affect LTPFS. Complications were reported more frequently after LMWA. Despite higher complication rates, LMWA seems a valid option for treatment of subcapsular tumors.